ANALISIS PENENTUAN STRATEGI PEMASARAN DENGAN KONSEP MARKETING MIX PADA DAYA TARIK WISATA GILI LAMPU LOMBOK TIMUR - Yona Floranika; Erri Supriyadi; I Wayan Nuada; Muharis Ali; I Gusti Ngurah Oka Widjaya; Indrapati Indrapati; I Wayan Bratayasa (Journal Of Responsible Tourism, 2022)
Gili Lampu is a marine tourism destination that has potential with uniqueness and characteristics that are not owned by other tourist destinations in the vicinity which are expected to attract large numbers of tourists, one way is to do marketing. This study will discuss the marketing strategy carried out by the Gili Lampu manager using the concept of the marketing mix, the aim is to find out the obstacles in the application of the strategy that has been carried out. This research method uses a qualitative method with a descriptive approach. The results of this study reveal that the marketing strategy carried out by the Gili Lampu manager uses the concept of a marketing mix, especially the 8p marketing mix, where for each 8p variable it has been carried out namely product, price, place, promotion, people, packaging, program and partnership. , there are several variables that are still not optimally carried out by the manager such as products, prices, promotions and programs. For this reason, it is very important to determine the right marketing strategy for tourist destinations because it will have a very large influence in increasing the number of tourist visits.